Analisis Perlindungan Hukum Terhadap Konsumen Atas Produk Skincare Ilegal - Alfarissa, Tiara; Thefirsly N, Chiquita; Raditya, Bariq; Putri, Lisa Angelie; Awalin, Hanif Fil; Sakti, Muthia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Beauty products have become a trend among people as a tool for self-care. Self-care to beautify your appearance, especially your face, is a natural thing because having bright, white, clean facial skin, free of acne and black spots is a dream. Business actors are taking advantage of the massive self-care trend by creating products for self-care such as skincare. Skincare is a product that can eliminate skin problems, for example removing black spots, acne, dullness, blackheads and so on. The large market opportunity for skincare products is certainly a profitable target for business actors. Unfortunately, this opportunity is actually exploited by business actors by targeting consumers who are looking for cheap goods with instant results. This research will discuss the legal consequences of selling illegal skincare products and forms of consumer protection for those who use illegal skincare. The purpose of this writing is to provide information to readers about the large number of skincare products that are widely circulated without BPOM permission and the importance of BPOM permission for skincare products that are distributed widely. In carrying out the preparation of writing research results using normative juridical research methods. The conclusion of this research is increasing monitoring of skincare distribution and testing by BPOM.